Estudo de caso-controle para avaliação dos fatores de risco relacionado ao acinetobacter baumannii oxa-23 resistêntes aos carbapenêmicos e avaliação da resistência frente à polimixina de pacientes hospitalizados no Paraná, Brasil - Vandresen, Débora Fiorentin (2020)
The increase in multidrug-resistant bacterial strains has been notorious in both developed and developing countries, causing global concerns to health systems Among the strains of microorganisms, Acinetobacter baumannii (A. baumannii) is classified as critical for public health policies due to its high resistance rate, especially in hospitals. The objective of this study was to characterize - molecularly and phenotypically - the bacterial samples taken from patients in a hospital in Paraná, correlating them with the patients’ risk factors and analyzing their epidemiology withing hospital infections and its resistance to Polymyxin. A case-control study was performed with 99 individuals who were hospitalized between 2017 to 2019 at the Regional Hospital (located in Francisco Beltrão, Paraná, Brazil). Demographic variables, origin of hospitalization and sector of hospitalization, use of invasive device and antimicrobials, surgical procedure, and patient outcome (hospital discharge/death) were analyzed. Also, microbiological data – including isolated microorganisms, the antimicrobial resistance profile, resistance genes and phenotypic tests - were collected. Cases samples were taken out of positive culture tests results for A. baumannii, which were recruited after manual testing followed by confirmation using Vitek 2 (bioMérieux®, Marcy-LÉtoile, France). The gene blaoxa-23 presence was analyzed using PCR at the LACEN-PR. Controls were those who did not developed colonization by A. baumannii. Cases and controls were matched by age (same age or ± 5 years), gender, and hospitalization sector. A logistic regression analysis was used to identify A. baumannii. associated risk factors. A. baumannii incidence was 0,21%, 0,15% and 0,17% in 2017, 2018 and 2019, respectively. Cases had higher length of hospitalization until the positive culture results (p < 0,001), were mostly admitted from other institutions (p = 0,038) and needed mechanical ventilation (p < 0,001). Moreover, higher relative cases of death (p = 0,024) were found in cases in comparison to controls, with deaths increasing over the years. It was also observed that all strains presented resistance to carbapenems and sensitivity to Polymyxin B when the microdilution method was used. Results show a clear need for activities involving surveillance and monitoring of patients with longer hospitalizations (especially in the ICU sector) and those using mechanical ventilation, thus indicating the importance of adopting prevention measures practices to avoid A. baumannii dissemination. This could decrease mortality rates. Also, the investigation emphasizes the use of reliable tests to investigate the resistance of A. baumannii to Polymyxin B.